Pengembangan Media Pembelajaran Berbasis Permainan Tradisional pada Materi Bilangan Cacah di Sekolah Dasar - Sasabila, Alesia; Sastrawati, Eka; Zahyuni, Violita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an mathematics learning media based on the traditional game bekel for whole number material in lower grade elementary school students. The research uses a Research and Development (R&D) approach with the ADDIE model consisting of analysis, design, and development stages. Data were collected through observation, interviews, and validation questionnaires involving experts in material, media, and language. The results of the analysis show that the learning process still relies on conventional media and lacks interactive elements, causing low student engagement. The developed product is designed using storyboard and includes bekel tools and instructional cards. Validation results indicate that the developed media meets validity criteria and is feasible to be tested further. This study concludes that the developed media has good validity and potential to support mathematics learning.